Realizing the witch : science, cinema, and the mastery of the invisible (2016)
The Wild Ride. The Sabbat. Child sacrifi ce. Diseases, ruin, and torture. The old hag. The kleptomaniac. The modern hysteric. Benjamin Christensen took the threads of phantasm and wove them into a fi lm thesis that would not talk about witches, but would give the witch life. Häxan is a document, an amplifi ed account of the witch insistent on its historical and anthropological qualities, presented through excesses so great that they toyed with his audience’s skepticism as much as their sensitivity. Christensen created an artistic work fi lled with irrationalities that not only made the witch plausible, but real. By the time Benjamin Christensen (1879–1959) began fi lming Häxan in 1921, he had already spent nearly three years conducting research for his fi lm and securing a studio in Copenhagen to accommodate his costuming and elaborate set designs. Häxan was not the Danish actor/director’s fi rst foray into fi lmmaking, but it would be his most ambitious. The silent fi lm was the most expensive ever produced in Scandinavia.1 The Swedish fi lm production com pany, Svensk Filmindustri, provided Christensen with funding (in addition to buying back the director’s own studio fac ility from creditors) in 1919 to make what Christensen called “a cultural– historical fi lm in seven acts.” With Swedish funding came a Swedish title for the fi lm (the Danish word for “witch” is heksen). The fi lm was shot in Copenhagen in 1921–22, and premiered in Stockholm in September 1922. Despite laborious planning, seemingly endless trou ble with censors, and the unpre ce dented scale of his pro ject, Häxan was only the fi rst of a trilogy imagined (but never realized) by Christensen— the other fi lms in his unfi nished series were tentatively titled Helgeninde (Saints [feminine]) and Ånder (Spirits).